PKM Pelatihan Pendampingan Web Profil Desa Tarikolot Sumedang - Saeful Anwar; Yudhistira Arie Wijaya; Fathurrohman; Arif Rinaldi Dikananda; Hilpad Hidayat (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Tarikolot Village in Sumedang has significant potential in various aspects, yet it remains underexposed due to the limited availability of information online. Many villages in Indonesia have not yet utilized digital technology to introduce their village profiles and potential to the public, resulting in missed opportunities for economic and social development. Through this Student Creativity Program (PKM), training and mentoring are provided for the creation and management of a village profile website for Tarikolot Village, aimed at enhancing the accessibility of information and promoting the village digitally.The objective of this program is to equip village officials and the community with the knowledge and skills to independently build, manage, and update the village profile website. The implementation methods include technical training on website development, content management workshops, and intensive mentoring in using digital platforms for village promotion. The expected outcome of this activity is the creation of an informative and easily accessible Tarikolot Village profile website, as well as improved digital information management skills among the villagers. It is anticipated that this website will increase the visibility of Tarikolot Village, attract investment, and improve the overall welfare of the village community.